The genus Bassus Fabricius, 1804 (Hymenoptera: Braconidae: Agathidinae) in China, with description of three new species. Issue 45 (10th December 2017) - Tang, Pu; Van Achterberg, Cornelis; Chen, Xue-Xin
ABSTRACT: Five species of Bassus Fabricius, are recognized to occur in China, of which three are new: Bassus guangxiensis sp. nov., Bassus levisulcus sp. nov. and Bassus robustus sp. nov. The new species are described and fully illustrated. Bassus albozonatus van Achterberg & Long, is recorded from China for the first time. A key to the Chinese species of the genus Bassus is provided.www.zoobank.org/urn:lsid:zoobank.org:pub:17297254-9E84-4D0F-AE8C-1F7264393137